Evaluación del desperdicio de alimentos: normas y acciones para fomentar la circularidad en Perú - Huiman Cruz, Alberto (Pontificia Universidad Católica del Perú, 2024)
Population growth generates a higher demand for food and, thereby the waste of larger quantities of food. The fight against this problem has been initiated in several countries through strict regulations that manage food waste: Peru has made proposals related to the use of food waste, however, they were ineffective when it became evident that there was a lot of waste The objective of this article is to analyze the management of food waste in Peru and the world, both in terms of regulations and situation; for this purpose, a bibliographic review was carried out taking into account the guidelines of circularity in food. The results obtained show deficiencies in the Peruvian and world regulatory framework, with the exception of Europe. It was found that the generation of food waste is abundant worldwide, especially in the hotel, restaurant and cafeteria sector, with portion size being the main cause. The countries coincide in their concern for the increase in waste and seek to frame themselves in the circularity model, in the case of Peru, this implies modifying and improving regulations with the participation of the actors involved. In view of this, a vision of sustainability is proposed in which the agricultural sector, the local economy, the supply chain, and technology intervene as factors that guarantee a sustainable food industry; as well as the legislative initiatives that seek to reduce food waste.

El crecimiento poblacional genera una mayor demanda alimenticia y, con ello, aumenta el desperdicio de alimentos. La lucha contra este problema inició en varios países con estrictas regulaciones que gestionan los residuos alimentarios: Perú ha realizado propuestas relacionadas con el aprovechamiento, sin embargo, resultaron ineficaces al evidenciarse cuantiosos desperdicios. El objetivo del artículo es analizar el manejo de residuos alimentarios en Perú y el mundo, tanto en normatividad y situación; para ello, se realizó una revisión bibliográfica tomando en cuenta los lineamientos de circularidad en los alimentos. Los resultados obtenidos demuestran deficiencias en el marco regulatorio peruano y mundial, con excepción de Europa. Se constató que la generación de residuos alimentarios a nivel mundial es abundante, especialmente en el sector de hotelería, restaurantes y cafetería, siendo el tamaño de raciones el principal causante. Los países coinciden en la preocupación por el aumento de los residuos y buscan enmarcarse en el modelo de circularidad, en el caso de Perú, implica modificar y mejorar la regulación con la participación de actores involucrados. Ante ello, se propone una visión de sostenibilidad en la que intervienen el sector agrario, la economía local, la cadena de suministro, y la tecnología como factores que garantizan una industria alimentaria sostenible; así como las iniciativas legislativas que buscan la disminución de los residuos alimentarios.
Food waste assessment: Standards and actions to promote circularity in Peru
Keywords: Food waste; Circular economy; Food industry; Sustainability; Peru; Residuos alimentarios; Economía circular; Industria de alimentos; Sostenibilidad; Perú; https://purl.org/pe-repo/ocde/ford#2.07.01